Measurement of the t(t)over-bar production cross section in p(p)over-bar collisions using dilepton events - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2007)
We present a measurement of the t (t) over bar pair production cross section in p (p) over bar collisions at root s=1.96 TeV utilizing approximately 425 pb(-1) of data collected with the D0 detector. We consider decay channels containing two high p(T) charged leptons (either e or mu) from leptonic decays of both top-daughter W bosons. These were gathered using four sets of selection criteria, three of which required that a pair of fully identified leptons (i.e., e mu, ee, or mu mu) be found. The fourth approach imposed less restrictive criteria on one of the lepton candidates and required that at least one hadronic jet in each event be tagged as containing a b quark. For a top quark mass of 175 GeV, the measured cross section is 7.4 +/- 1.4(stat)+/- 1.0(syst) pb and for the current Tevatron average top quark mass of 170.9 GeV, the resulting value of the cross section is 7.8 +/- 1.8(stat+syst) pb.